Front Range Fuels Treatment Partnership: 2010 annual report - Front Range Fuels Treatment Partnership, author; Colorado State Forest Service, author; United States. National Park Service, author; Rocky Mountain Research Station (Fort Collins, Colo.), author; United States. Forest Service, author (Colorado State University. Libraries, 2011)
The FRFTP reports describe fuels treatments accomplished on private, state and federal lands along Colorado's Front Range by FRFTP forest management agencies: Colorado State Forest Service, National Park Service and U.S. Forest Service. These reports also highlight relevant scientific research completed by the Rocky Mountain Research Station and include annual reports for the Front Range Roundtable.
FRFTP: 2010 annual report
2010 FRFTP annual report
2010 summary of accomplishments.
Keywords: forests and forestry; Colorado; forest health; forest management